Ultrathin Piezoelectric Resonators Based on Graphene and Free‐Standing Single‐Crystal BaTiO3. Issue 44 (3rd October 2022) - Lee, Martin; Renshof, Johannes R.; van Zeggeren, Kasper J.; Houmes, Maurits J. A.; Lesne, Edouard; Šiškins, Makars; van Thiel, Thierry C.; Guis, Ruben H.; van Blankenstein, Mark R.; Verbiest, Gerard J.; Caviglia, Andrea D.; van der Zant, Herre S. J.; et al.
Abstract: Suspended piezoelectric thin films are key elements enabling high‐frequency filtering in telecommunication devices. To meet the requirements of next‐generation electronics, it is essential to reduce device thickness for reaching higher resonance frequencies. Here, the high‐quality mechanical and electrical properties of graphene electrodes are combined with the strong piezoelectric performance of the free‐standing complex oxide, BaTiO3 (BTO), to create ultrathin piezoelectric resonators. It is demonstrated that the device can be brought into mechanical resonance by piezoelectric actuation. By sweeping the DC bias voltage on the top graphene electrode, the BTO membrane is switched between the two poled ferroelectric states. Remarkably, ferroelectric hysteresis is also observed in the resonance frequency, magnitude and Q ‐factor of the first membrane mode. In the bulk acoustic mode, the device vibrates at 233 GHz. This work demonstrates the potential of combining van der Waals materials with complex oxides for next‐generation electronics, which not only opens up opportunities for increasing filter frequencies, but also enables reconfiguration by poling, via ferroelectric memory effect. Abstract : Piezoelectric resonators are ubiquitous elements for frequency filtering in telecom devices. A piezoelectric resonator consisting of a suspended van der Waals heterostructure of ultrathin single‐crystal free‐standing BaTiO3 sandwiched between graphene sheets is reported. The heterostructure is piezoelectrically driven into a flexural motion and the resulting mechanics shows ferroelectric switching. The bulk‐mode resonance at 233 GHz is the highest reported.